Peran Hukum dalam Penertiban Juru Parkir Liar di Kota Medan Ditinjau dalam Perspektif Hukum Pidana - Join Prasanta Karo Karo; Sonya Airini Batubara; Geriel Zefanya .; Reza Farhansyah Reza Farhansyah (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
The practice of unauthorized parking attendants in Medan City gives rise to issues concerning public order and legal certainty. This study aims to analyze the legal framework, law enforcement and the role of criminal law regarding this practice, employing a normative legal research method alongside statutory and conceptual approaches. The findings indicate that fees collected by unauthorized parking attendants are not automatically categorized as acts of corruption, as they do not necessarily involve an abuse of authority or financial loss to the state; instead, such actions are more appropriately classified as illicit levies, extortion, or other criminal offenses, depending on the specific legal facts. It is recommended that the local government strengthen integrated supervision, implement electronic parking systems, conduct periodic law enforcement operations and take firm action against unauthorized parking operators to enhance legal certainty and public protection. Consequently, a collaborative synergy between the local government, law enforcement and the public is essential to foster a parking management system that is orderly, transparent and just.